Digital endpoints for self‐administered home‐based functional assessment in pediatric Friedreich's ataxia. Issue 9 (6th August 2021) - Mueller, Arne; Paterson, Elaine; McIntosh, Avery; Praestgaard, Jens; Bylo, Mary; Hoefling, Holger; Wells, McKenzie; Lynch, David R.; Rummey, Christian; Krishnan, Michelle L.; Schultz, Meredith; Malanga, C. J.
Abstract: Background: Friedreich's ataxia is an inherited, progressive, neurodegenerative disease that typically begins in childhood. Disease severity is commonly assessed with rating scales, such as the modified Friedreich's Ataxia Rating Scale, which are usually administered in the clinic by a neurology specialist. Objective: This study evaluated the utility of home‐based, self‐administered digital endpoints in children with Friedreich's ataxia and unaffected controls and their relationship to standard clinical rating scales. Methods: In a cross‐sectional study with 25 participants (13 with Friedreich's ataxia and 12 unaffected controls, aged 6–15 years), home‐based digital endpoints that reflect activities of daily living were recorded over 1 week. Domains analyzed were hand motor function with a digitized drawing, automated analysis of speech with a recorded oral diadochokinesis test, and gait and balance with wearable sensors. Results: Hand‐drawing and speech tests were easy to conduct and generated high‐quality data. The sensor‐based gait and balance tests suffered from technical limitations in this study setup. Several parameters discriminated between groups or correlated strongly with modified Friedreich's Ataxia Rating Scale total score and activities of daily living total score in the Friedreich's ataxia group. Hand‐drawing parameters also strongly correlated with standard 9‐hole peg test scores. Interpretation: Deploying digital endpoints in home settings is feasible in this population, results in meaningful and robust data collection, and may allow for frequent sampling over longer periods of time to track disease progression. Care must be taken when training participants, and investigators should consider the complexity of the tasks and equipment used.